Meta-analysis in genome-wide association studies: application to type 2 diabetes - Zeggini, Eleftheria (Henry Stewart Talks, 2008)
Genetic architecture of common complex diseases, Genome-wide association scans, Genome-wide association scan methodology, Application to type 2 diabetes genome-wide association scan data